Beyond the commuter belt: graduates’ plans for migration and demographic change in rural areas: The case of the Haßberge district in Lower Franconia - Chilla, Tobias; Morhart, Tobias; Braun, Boris (Raumforschung und Raumordnung | Spatial Research and Planning, 2008)
The population of many regions in rural areas declines as mainly young adults leave. Simultaneously, only few people move into these areas if processes like suburbanisation do not play a substantial role. In this situation, young adults must be regarded as a crucial group for the future of any region. Demographic, economic, and societal prosperity depends on them to a large extent. At the same time, school graduates are increasingly forced to be more and more mobile by changing and more volatile labour markets. The article focuses on the motivations of graduates while making their decisions to leave their home district or to stay. Based on this analysis, it asks which political instruments are appropriate in these regions beyond ‘commuter-belts’. Considering the local context, the authorities have to combine policies and instruments including family policy, regional marketing and educational aspects. The empirical findings are based on a case study in the Haßberge district in Northern Bavaria.
Keywords: Demographic change; Internal migration; Education geography; Geography of employment; Bavaria